Penerapan Teori Positivisme Hukum dalam Penyelesaian Perkara Kepailitan di Indonesia - Yofi Permatasari; Rasji (CV Rewang Rencang, 2024)
This research aims to find out the concept of legal positivism theory in the Indonesian legal system along with its application in bankruptcy cases in Indonesia. The research method used is a literature study with the nature of descriptive research and the type of data used is secondary data through qualitative analysis. The results of the study show that legal certainty is able to provide guarantees to the community of the rights they have in order to realize a fair and proportionate law. In bankruptcy, there is the influence of positivism through Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations has applied several principles, namely the principle of balance, the principle of business continuity, the principle of justice and the principle of integrity.